PERILAKU REMAJA PECANDU ROKOK SISWA SMP DI DESA GUNUNG KESIANGAN KECAMATAN BENAI KABUPATEN KUANTAN SINGINGI - Bita Febri; Swis Tantoro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The phenomenon of smoking behavior in adolescents is now increasingly alarming and seemed to have become a trend among both junior and high school students, even a small percentage of elementary school students have also shown their smoking behavior. This study aims to determine the impact of the behavior and the factors that influence smoking behavior in adolescents conducted on 10 junior high school students. Research using qualitative methods with accidental sampling approach. Data were collected using an open questionnaire and semi-structured interviews, while data analysis is done with thematic analysis and descriptive. Which revealed the smoking behavior in adolescents, the average starting age of 12 years. Smoking behavior lived with friends, shop, hangout, and sometimes at school. The first smoking experience coughing and dizziness, but still there is a desire to try it again because it was fun with friends. Further experience feel fresh and comfortable when smoking. In addition, it also gives a sense of calm, relaxed, passion, and gives the impression of a more mature, and raise the prestige within the peer group. The study also reveals behind the feelings above the teens did not feel afraid and worried about the impact of smoking. Impact on kesehatanpun've often felt dizzy.Keywords: Smoking, behavior, Teens